The Long, Hot Summer of 1967 - McLaughlin, M. author. aut Link
XIII, 227 p.
Keywords: It seemed at times during the 1960s that America was caught in an unending cycle of violence and disorder. Successive summers from 1964-1968 brought waves of urban unrest, street fighting, looting, and arson to black communities in cities from Florida to Wisconsin, Maryland to California. In some infamous cases like Watts (1965), Newark (1967), and Detroit (1967), the turmoil lasted for days on end and left devastation in its wake: entire city blocks were reduced to burnt-out ruins and scores of people were killed or injured mainly by police officers and National Guardsmen as they battled to regain control. This book takes the pivotal year of 1967 as its focus and sets it in the context of the long, hot summers to provide new insights into the meaning of the riots and their legacy. It offers important new findings based on extensive original archival research, including never-before-seen, formerly embargoed and classified government documents and newly released official audio recordings.